2021
DOI: 10.1144/jgs2020-116
|View full text |Cite
|
Sign up to set email alerts
|

Fluid–rock interactions along detachment faults during continental rifting and mantle exhumation: the case of the Urdach lherzolite body (North Pyrenees)

Abstract: The North Pyrenean Zone (NPZ) corresponds to the paleo-passive margin of the North Iberia plate at the foot of which subcontinental mantle exhumed during Albian times. Rare bodies of exhumed mantle rocks associated with strongly sheared lenses of continental crust are scattered among the NPZ metasediments. In the Urdach massif (Chaînons Béarnais), significant fluid flow occurred along a major décollement at the basement-Trias interface. Fluids with a broad range of salinity (10 to 38 wt.% NaCl equiv.), indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…10D and E). Such a process was inferred in the case of the late silicification at Urdach: mixing trends between saline and dilute end-members are typical of the early silicification, and during later stages, quartz cement formed from hypersaline brine suggesting that the unconformity was isolated due to the deposition of the Cenomanian flysh, limiting or stopping the venue of seawater (Nteme Mukonzo et al, 2021).…”
Section: Role Of Salt and Brines During The Rifting Stagementioning
confidence: 86%
See 2 more Smart Citations
“…10D and E). Such a process was inferred in the case of the late silicification at Urdach: mixing trends between saline and dilute end-members are typical of the early silicification, and during later stages, quartz cement formed from hypersaline brine suggesting that the unconformity was isolated due to the deposition of the Cenomanian flysh, limiting or stopping the venue of seawater (Nteme Mukonzo et al, 2021).…”
Section: Role Of Salt and Brines During The Rifting Stagementioning
confidence: 86%
“…Several studies consider these water-rock interactions as representative of syn-rift processes and are dated in some instances (albitisation: Poujol et al, 2010Mgmetasomatism: Boulvais et al, 2006;Boutin et al, 2016; breccias with silicifications and carbonate cements: Debroas et al, (2010), Asti et al, (2019), Incerpi et al, 2020, Nteme Mukonzo et al, 2021; see later the compilation of available ages). Table 1 provides details about localities (host-rock, inferred ages of the formation when available).…”
Section: New Sampling and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Angrand et al, 2020). Since the concepts of crustal hyper-extension and sub-continental mantle exhumation were applied in the NPZ (Jammes et al, 2009;Lagabrielle et al, 2010;Lagabrielle and Bodinier, 2008), the role of salt tectonics during rifting and inversion has been emphasized as a major element of the Pyrenean rift evolution based on numerical experiments (e.g., Grool et al, 2019;Duretz et al, 2019;Jourdon et al, 2020) and field studies (Jammes et al, 2010;Lagabrielle et al, 2020). Despite this important effort, the temporal and spatial relationships between the basement-cover decoupling in the Triassic evaporites and mantle exhumation during rifting…”
Section: Introductionmentioning
confidence: 99%
“…To date, the formation of breccias in or near the base of early Cretaceous extensional basins in the Pyrenees have been attributed to :(i) debris flows reworking footwall rocks of high-angle normal fault scarps (Debroas, 1990(Debroas, , 1987Souquet et al, 1985) or low-angle detachment systems (Jammes et al, 2009;Masini et al, 2014), (ii) dissolution-collapse brecciation processes during pre-and syn-rift salt mobilization (Canérot et al, 2005(Canérot et al, , 2004Canérot and Lenoble, 1993;Labaume and Teixell, 2020), (iii) hydraulic fracturing and dolomitization caused by rift-related fluid activities (Incerpi et al, 2020b;Salardon et al, 2017), (iv) fluidassisted (brines) tectonic brecciations along extensional decollement localized in the Triassic evaporites and the pre-rift limestones (Clerc et al, 2016(Clerc et al, , 2015Lagabrielle et al, 2020;Mukonzo et al, 2021) or found in association with ultramafic rocks (Asti et al, 2019;Clerc et al, 2012;de Saint Blanquat et al, 2016;Lagabrielle et al, 2016Lagabrielle et al, , 2019a in-situ topbasement cataclastic breccias across low-angle detachment fault (Masini et al , 2014;Cadenas et al, 2021). These studies are based on observations made at different locations along the strike of the Pyrenean rift and therefore are valuable only at a given rift segment.…”
Section: Introductionmentioning
confidence: 99%